Spirometry Findings in Patients with Chronic Obstructive Pulmonary Disease - Shrestha, Ashis; Bajrachraya, Sumana (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Clinical diagnosis of chronic obstructive pulmonary disease is often not accurate and treated for prolong duration. This study explores the use of pulmonary function test to confirm the diagnosis and further management of such patients. Methods: This was a cross sectional study conducted at Patan Hospital, Patan Academy of Health Sciences, Nepal. All patients coming for spirometry between June 2012 and May 2013 with the clinical diagnosis of chronic obstructive pulmonary disease were enrolled in the study. Results: Out of 338 patients with clinical diagnosis of chronic obstructive pulmonary disease that underwent spirometry, 80 (23.7%) patients had ratio of forced expiratory volume in one second and forced vital capacity less than 70%. Out of these 80 patients, 50 (14.8%) had irreversible airway obstruction and 30 (8.9%) had reversible airway obstruction. Patient with normal spirometry findings was 258(76.3%). Conclusions: Clinically diagnosed chronic obstructive pulmonary disease is best confirmed by spirometry for optimum management. Plain Language Summary: The study was done to see whether the clinical diagnosis of COPD is accurate of not. The study found that most of the patient diagnosed as COPD did not have the disease on spirometry. So, diagnosis of COPD should always be aided by spirometry before starting long term treatment. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13014 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):33-35